2022
DOI: 10.1080/20008198.2021.2024974
|View full text |Cite
|
Sign up to set email alerts
|

The moderation of maternal parenting on the association of trauma, dissociation, and psychosis in depressive inpatients

Abstract: Background The effect of dissociation and parenting style on the relationship between psychological trauma and psychotic symptoms has not previously been investigated. Objective The aim of this study was to develop a moderated mediation model to assess whether the association between psychological trauma and psychotic symptoms is mediated by dissociation and moderated by parental maltreatment. Methods Inpatients with major depressive disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Five studies have compared the severity of DS in patients with BD and major depressive disorder (MDD), have measured DS during depressive episodes. In four of these studies, DS were more prominent in BD than in MDD ( 22 , 26 , 30 , 38 ), while in the other, they were comparable ( 44 ). Studies comparing the severity of DS between BD and other, non-affective psychiatric disorders found that DS were significantly less in BD than in somatoform disorders and DD ( 18 , 19 , 32 ), complex post-traumatic stress disorder (PTSD) ( 32 ), atypical psychosis in adolescents ( 20 ), and borderline personality disorder ( 36 ).…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Five studies have compared the severity of DS in patients with BD and major depressive disorder (MDD), have measured DS during depressive episodes. In four of these studies, DS were more prominent in BD than in MDD ( 22 , 26 , 30 , 38 ), while in the other, they were comparable ( 44 ). Studies comparing the severity of DS between BD and other, non-affective psychiatric disorders found that DS were significantly less in BD than in somatoform disorders and DD ( 18 , 19 , 32 ), complex post-traumatic stress disorder (PTSD) ( 32 ), atypical psychosis in adolescents ( 20 ), and borderline personality disorder ( 36 ).…”
Section: Resultsmentioning
confidence: 94%
“…DS scores have been associated with the severity of psychotic symptoms ( 42 , 44 ); both positive and null results have been reported for associations between DS and depressive symptom severity ( 31 , 41 ). DS severity has also been associated with general symptom severity across psychopathological dimensions ( 31 ), with the severity of symptoms of social anxiety, panic disorder and obsessive-compulsive disorder ( 33 , 41 ), with the presence of mixed symptoms ( 42 ), with suicide attempts ( 40 , 42 ) and with aggression ( 42 ).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…This study derived data from two projects which aimed to investigate the stability of self‐reported childhood interpersonal adversity and relationships among interpersonal adversity, psychiatric status, and socio-cognitive functions. 30 These investigations were approved by the Institutional Review Board of Kai-Syuan Psychiatric Hospital on 30th Dec 2014 and 1st May 2017 (KSPH-2014-34 and KSPH-2017-04) and conducted in accordance with the current revision of the Declaration of Helsinki and national legal requirements (Human Subjects Research Act, Taiwan). All participants signed written informed consent after the study had been explained in detail.…”
Section: Methodsmentioning
confidence: 99%